The profile of temporary teachers in São Paulo State public education system - José Quibao Neto; José Marcelino de Rezende Pinto (Fineduca, 2016)
The working conditions of teachers have been object of several debates and studies in Brazil. More recently, issues regarding their working contract situation have acquired prominence, since many of those who work in public schools in Brazil did not enter the career through a public contest, thus having different employment relationships with the State. Considering the presence of several teachers with a temporary contract in São Paulo State Public Education System, this study aimed to compare their profile with different working contract conditions in this network. For that, it was used the School Census microdata from 2011 to 2013, a databank developed by the Anísio Teixeira National Institute of Educational Studies and Research (Inep), an autarchy linked to the Ministry of Education. In general, it was found that the significant differences between public/tenured and temporary teachers are largely related with the age group and, with less intensity, with their race/skin color. In contrast, it was found that the public/tenured and the temporary teachers have a similar profile concerning the other variables: gender, schooling and type of Higher Education Institution.